The correlation between neutrophil - lymphocyte ratio and neoadjuvant chemoradiotherapy response prediction in locally advanced rectal cancer - Karahan, Veysel; Üstün, Mehmet; Uğurlu, Levent; Kaya, Tayfun; Emiroglu, Mustafa; Aydın, Cengiz (My University, 2018)
Objective: The determination of predictive factors for neoadjuvant chemoradiotherapy response in locally advanced rectum cancer is critical concerning treatmentmanagement. We aim to analyze the predictive value of clinicopathologic findings oflocally advanced rectal cancer patients before neoadjuvant chemoradiotherapy.Methods: Fifty patients who were diagnosed with locally advanced rectum cancerwithout distant metastasis and underwent surgery after the neoadjuvant CRT treatment in the department of general surgery, between January 2008-2015 were analyzed.Results: Twenty three (46%) cases did not yield pathologic response, while 27 (54%)responded to neoadjuvant chemoradiotherapy. There was no statistically significantdifference between the responding, and the non-responding groups in terms of meanages and gender distribution (p=0.360, p=0.665), the distribution of tumor distancefrom anal verge (p=0.777), pathologic types (p=0.451), pre-op T stage and N stage(p=0.322 and p=0.321), type of surgical procedures (p=0.061, p=0.200), levels of CEA(p=0.195), and PLR (p=0.704). The possiblity of not responding in cases with NLR> 4was statistically significantly different from those with NLR <4 (95% ConfidenceInterval: 2.043-62.915) compared to NLR <4 cases (p=0.005).Conclusion: NLR can be used as a predictive factor in locally advanced rectal cancerbefore initiating neoadjuvant chemoradiotherapy.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Patoloji; Onkoloji